The Influence of Conjugated Linoleic Acid Enriched Tallow on Egg Hatchability and Quality in Chicken - Aydin, R.; Cook, M.E. (International Journal of Poultry Science, 2005)
Dietary conjugated linoleic acid (CLA) was shown to increase the level of saturated fatty acids in egg yolk, alter interior egg quality, and induce embryo mortality in fertile eggs. Since CLA may soon be used as an animal feed supplement, the objective of this study was to determine if feeding chickens tallow from beef cattle fed a CLA-supplemented diet would induce embryo mortality and cause changes in egg quality. Single Comb White Leghorn laying hens (10 per treatment) were fed a diet containing 0.5% canola oil (CO), 0.5% CLA (CLA), 10% regular tallow (RT), 9.5% regular tallow plus 0.5% CLA (RT+CLA), 10% tallow from beef cattle fed 1% CLA (TCLA1), or 10% tallow from beef cattle fed 2.5% CLA (TCLA2.5) for 18 d. For hatchability studies, hens were artificially inseminated weekly. Eggs were collected daily, stored at 15oC for 24 h, and then incubated. Twenty eggs per treatment were stored at 4oC for 30 d and analyzed for pH. After 18 d of feeding, 3 hens per group were euthanized with carbon dioxide exposure and liver and adipose tissue samples were obtained. Fat from yolk, liver and adipose tissue were extracted for fatty acid analysis. After the 8th d of feeding, embryo mortality was 100% in CLA group versus 7, 9, 5, 6, and 7% in CO, RT, RT+CLA, TCLA1, and TCLA2.5, respectively. Relative CLA levels (% of fatty acids) of yolk from CO, CLA, RT, RT+CLA, TCLA1, and TCLA2.5 were 0, 2.31, 0.99, 1.67, 1.18, and 1.35%, respectively. Diets containing CLA and RT+CLA resulted in increased C16:0 and C18:0 and decreased C16:1(n-7) and C18:1(n-9) in the egg yolk. The CLA but not TCLA1 or TCLA2.5 diet resulted in decreased levels of C20:4(n-6) in yolk and liver compared to CO. Yolk pH increased and albumen pH decreased in the eggs from the CLA relative to CO (8.09 and 8.63 versus 6.13 and 9.04, respectively). Abnormal pH changes did not develop in the eggs from CO, RT, RT+CLA, TCLA1 and TCLA2.5. These results showed that tallow from beef cattle fed CLA or tallow supplemented with CLA had no adverse effects on hatchability and egg quality.